1988
DOI: 10.1210/endo-122-4-1521
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Thyroxine from the Mother to the Rat Fetus Near Term: Effects on Brain 3,5,3'-Triiodothyronine Deficiency*

Abstract: It has recently been shown that thyroid hormones are transferred from the mother to the developing rat embryo early in gestation, before the onset of fetal thyroid function. We have now studied whether there is transfer of T4 from the mother to the fetus late in gestation when the fetal thyroid is impaired. Normal and thyroidectomized females were mated, given a goitrogen [methimazole (MMI)], starting before the onset of fetal thyroid function and until term, alone or together with a constant infusion of T4 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…There were no apparent MMI treatment-related effects on the offspring's body weights over the 3–4 PND. As expected [4], [26], the INTACT pups on the tap water recorded normal size and growth during development, while defects due to the MMI treatment in CH rats were evident by a reduction in body weight (Supplementary File S3; panel A) and tail length (Supplementary File S3; panel B) from the second week of life. Upon weaning on PND30, biochemical hypothyroidism was shown, and significantly low circulating T3 (pg/ml) (9.93±0.66 vs. 7.80±0.83; P  = 0.0008) and elevated TSH (ng/ml) (2.73±2.04 vs .…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…There were no apparent MMI treatment-related effects on the offspring's body weights over the 3–4 PND. As expected [4], [26], the INTACT pups on the tap water recorded normal size and growth during development, while defects due to the MMI treatment in CH rats were evident by a reduction in body weight (Supplementary File S3; panel A) and tail length (Supplementary File S3; panel B) from the second week of life. Upon weaning on PND30, biochemical hypothyroidism was shown, and significantly low circulating T3 (pg/ml) (9.93±0.66 vs. 7.80±0.83; P  = 0.0008) and elevated TSH (ng/ml) (2.73±2.04 vs .…”
Section: Resultssupporting
confidence: 73%
“…Within 24 h after birth, excess pups were removed so that 8 pups were kept per dam. The indirect MMI exposure method (i.e., through maternal milk) utilized in this experiment has been extensively employed to induce a transitory congenital-neonatal hypothyroidism (CH) for the determination of short- and long-term physiological effects [4], [26], [29], [30]. Briefly, 0.02% MMI was administered in the drinking water for pregnant rats from GD12 until weaning at post-natal day (PND) 30, which is when pups were mature enough to support their own nutritional needs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibi tion of TRH-induced TSH release can be expected to become increasingly sensitive to Tj concentrations as gestational age ad vances [26], Thirdly, the decrease in the fetal TSH/ FT4 ratio also suggests that the thyroid gland becomes progressively more responsive to TSH during the second half of pregnancy [5,9], The placenta is freely permeable to thy rotropin-releasing hormone, IgG, and drugs used to treat thyroid disease, such as pro pylthiouracil, methimazole, iodine and pro pranolol [27], Placental transfer of thyroid hormones has been demonstrated in animal experiments [29]. Previous data from hu man neonatal cord blood have suggested that small amounts of T3 cross the placenta when maternal concentrations are high, whereas at physiologic concentrations pla cental transfer is limited [4], Recently, it has been demonstrated in a rat model that physiologic doses of T3 are substantially transferred into the fetal compartment [18,30]. Interestingly, we have observed a sig nificant correlation between maternal TT3 and fetal TT4 and T3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because fetal thyroid functions in rats begin at approximately GD 17 (Gilbert and Zoeller, 2010), the MMI administration started on GD 15. MMI is able to pass through the placenta and reach the fetuses during gestation (Marchant et al, 1977;De Escobar et al, 1988;Sack et al, 1995), and it is excreted into breast milk and taken by pups on PNDs (Johansen et al, 1982;Cooper, 1984). The date of birth was designated PND 0.…”
Section: Subjectmentioning
confidence: 99%